Effectiveness of Imago Therapy on Cognitive Flexibility and Post-Traumatic Growth in Women Affected by Extramarital Affairs - Nemati, Neda; Oraki, Mohammad; Saffarinia, Majid (Applied Family Therapy Journal (AFTJ), 2024)
Objective: The present study aimed to determine the effectiveness of Imago therapy on cognitive flexibility and post-traumatic growth in women affected by extramarital affairs. Methods: The research community included all women affected by extramarital affairs in the city of Isfahan (including the Nik Ovin Psychological Clinic and the Hazrat Abolfazl Charity Institute) in the spring of 2024. Accordingly, a group of women affected by extramarital affairs was randomly divided into two groups: an experimental group (15 individuals) and a control group (15 individuals). The experimental group received Imago therapy sessions, while the control group received no treatment. The data were analyzed using repeated measures tests with SPSS software version 23. Findings: The findings indicated that Imago therapy was effective in enhancing psychological flexibility and its subscales, as well as post-traumatic growth and its subscales, in women affected by extramarital affairs (P < 0.05). Conclusion: The obtained results showed that Imago therapy could be utilized as an effective approach for improving women affected by extramarital affairs, playing a significant role in enhancing their quality of life.